Design of Plant Maintenance Equipment Using HMI and PLC Omron CPMIA 40CDR - Imam Asbabil Khoer (FIDELITY : Jurnal Teknik Elektro, 2019)
Generally, plant maintenance can be done in two ways: manual (using humans with makeshift tools) and mechanical (using machine technology or robots). Plant maintenance done manually is watering and eradicating pests and diseases that do not necessarily do it and can harm humans themselves. Mechanically doing the same job has advantages, namely being faster, routine, and reducing workplace accidents. In the plant maintenance process at this time, there are still essential aspects for research, especially for the design of tools. The manual maintenance process's weakness is that performing sensory tasks in a large capacity takes a very long time. To overcome these limitations, a mechanical approach with automation technology is used to make it more effective and efficient. Therefore, the design of a watering device or plant maintenance is expected to overcome these problems. The use of human labor (manual) is not harmful but has drawbacks, including inconsistency with time and very time-consuming work. In the existing maintenance machine design research, there are various types. In this research, the design of the tool that will be carried out is to try to combine plant maintenance with a microcontroller automatic control system which is arranged using a servo motor motion system and several other motors which are expected to have an effective working system and excellent quality of maintenance results, for the cottage industry industrial enterprise.